A Case Report of Metastatic Renal Cell Carcinoma Causing Corticobasal Syndrome - Jensen, Melanie P. (Clin Neuropathol, 2021)
We present a case report of a patient with a history of renal cell carcinoma in which corticobasal syndrome had been diagnosed ante-mortem. However distinguishing features of corticobasal degeneration pathology were absent at post-mortem. Instead, neuropathological examination revealed features consistent with the patient’s history of renal cell carcinoma: micrometastatic renal cell carcinoma in cerebellar and cerebral white matter, including within the gyral white matter of the primary motor and somatosensory cortices. There was also Purkinje cell loss and mild lymphocytic inflammation in the cerebellum, but the significance of this was unclear. A number of ‘corticobasal degeneration mimics’ have been described in the literature; but micrometastatic carcinoma causing corticobasal syndrome is a novel finding. This case expands the range of clinical disorders which may mimic corticobasal degeneration to include micrometastatic carcinoma.